2007
DOI: 10.1007/s00442-007-0667-5
|View full text |Cite
|
Sign up to set email alerts
|

Low stocks of coarse woody debris in a southwest Amazonian forest

Abstract: The stocks and dynamics of coarse woody debris (CWD) are significant components of the carbon cycle within tropical forests. However, to date, there have been no reports of CWD stocks and fluxes from the approximately 1.3 million km(2) of lowland western Amazonian forests. Here, we present estimates of CWD stocks and annual CWD inputs from forests in southern Peru. Total stocks were low compared to other tropical forest sites, whether estimated by line-intercept sampling (24.4 +/- 5.3 Mg ha(-1)) or by complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
2
17

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 39 publications
3
71
2
17
Order By: Relevance
“…Comparing with similar studies from other tropical rain-forests, this current finding was lower than in Peru in which dead wood accounted for 7.5-9.3% of total AGB (Baker et al 2007). Pregitzer & Euskirchen (2004) reported that the mean C pool of woody debris across tropical forests amounted to 10% of the total carbon stocks.…”
Section: Discussioncontrasting
confidence: 67%
“…Comparing with similar studies from other tropical rain-forests, this current finding was lower than in Peru in which dead wood accounted for 7.5-9.3% of total AGB (Baker et al 2007). Pregitzer & Euskirchen (2004) reported that the mean C pool of woody debris across tropical forests amounted to 10% of the total carbon stocks.…”
Section: Discussioncontrasting
confidence: 67%
“…Our current understanding suggests that CWD stocks generally decrease from north-eastern to south-western Amazonia (Baker et al 2007;Chao et al 2009a). Spatial variation in CWD stocks across the landscape may respond both to short-term climatic disturbances (e.g.…”
Section: Introductionmentioning
confidence: 91%
“…Of the different stocks, above-ground biomass is most often assessed in tropical forests, however coarse woody debris (CWD) is also an essential component because of its role in biogeochemical cycles (Chambers et al 2000;Clark et al 2002;Wilcke et al 2005;Palace et al 2008). Within tropical forests, CWD accounts for 6 to 25% of total above-ground carbon stocks (Nascimento and Laurance 2002; Rice et al 2004;Baker et al 2007; Palace et al 2012), implying a total pan-Amazon CWD carbon stock of ca. 10 Pg (Chao et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los resultados muestran -1 que estos bosques acumulan 4.2 a 11.1 Mg C ha de madera muerta sobre el suelo. Estos valores de necromasa están en el rango menor de los valores reportados para la cuenca amazónica (0 a >80 Mg C; Baker et al, 2007) y equivalen a aquellos reservorios de bosques de arena blanca en Venezuela. La baja acumulación de madera muerta sobre el suelo puede estar relacionada a la baja productividad de los bosques como es el caso de los bosques de arena blanca (Malhi et al, 2004).…”
Section: Almacenamiento De Carbono Sobre El Suelounclassified